Oxygen uptake kinetics: historical perspective and future directions - Hughson, R. L. (Applied Physiology, Nutrition, and Metabolism, 2009)
Oxygen uptake has been studied in the transitions between rest and exercise for more than 100 years, yet the mechanisms regulating the rate of increase in oxidative metabolism remain controversial. Some of the controversy is a consequence of incorrect interpretations of kinetic parameters describing amplitude and time constant relationships, whereas other factors relate to an incomplete framework for interpretation of experimental results. In this review, a new conceptual 3-dimensional model is proposed to explore the intracellular environment of skeletal muscle in the rest-to-exercise transition. The model incorporates the so-called "metabolic inertia" describing the increases in metabolic substrates and enzyme activation, along with the dynamic changes in intracellular partial pressure of oxygen (PO2). Considerable evidence exists during normal submaximal exercise challenges for an effect of changes in O2 delivery to working muscles affecting the intracellular PO2 (displayed on the x axis) and the high energy phosphate concentration (y axis) during steady-state exercise as well as the transitions from rest to exercise. The z axis incorporates a hypothetical description of metabolic inertia that is enhanced by increased enzyme activation and production of metabolic substrates. Specific examples are given that describe how this axis can affect oxygen uptake kinetics within the context of changing intracellular PO2 and energetic states. Oxidative metabolism at the onset of exercise is regulated by a dynamic balance of O2 transport and utilization mechanisms and is not limited solely by metabolic inertia.